Modulation of Synaptic Plasticity in the Cortex Needs to Understand All the Players - Meunier, Claire N. J.; Chameau, Pascal; Fossier, Philippe M. (Frontiers in Synaptic Neuroscience, 2017)
The PreFrontal Cortex (PFC) is involved in cognitive tasks such as working memory, decision making, risk assessment and regulation of attention. These functions performed by the PFC are supposed to rely on rhythmic electrical activity generated by neuronal network oscillations determined by a precise balance between excitation and inhibition (E/I balance) resulting from the coordinated activities of recurrent excitation and feedback and feedforward inhibition. Functional alterations in PFC functions have been associated with cognitive deficits in several pathologies such as major depression, anxiety and schizophrenia. These pathological situations are correlated with alterations of different neurotransmitter systems (i.e. serotonin, dopamine, acetylcholine…) that result in alterations of the E/I balance. The aim of this review is to cover the basic aspects of the regulation of the E/I balance as well as to highlight the importance of the complementarity role of several neurotransmitters in the modulation of the plasticity of excitatory and inhibitory synapses. We illustrate our purpose by recent findings that demonstrate that serotonin and dopamine cooperate to regulate the plasticity of excitatory and inhibitory synapses targeting layer 5 pyramidal neurons of the PFC and to fine tune the E/I balance. Using a method based on the decomposition of the synaptic conductance into its excitatory and inhibitory components, we show that concomitant activation of D1Rs and 5-HT1ARs, through a modulation of NMDA receptors, favors Long Term Potentiation (LTP) of both excitation and inhibition and consequently does not modify the E/I balance. We also demonstrate that activation of D2-receptors requires functional 5-HT1ARs to shift the E-I balance towards more inhibition and to favor LTD of excitatory synapses through the activation of GSK3β (glycogen synthase kinase 3). This cooperation between different neurotransmitters is particularly relevant in view of pathological situations in which alterations of one neurotransmitter system will also have consequences on the regulation of synaptic efficacy by other neurotransmitters. This opens up new perspectives in the development of therapeutic strategies for the pharmacological treatment of neuronal disorders.